Pelatihan Pengolahan Limbah Kayu Mahoni (Swietenia Mahagoni) Pada BUMDes Banjarwaru - Radhi Ariawan; Nur Akhlis Sarihidaya Laksana; Unggul Satria Jati; Roy Aries Permana Tarigan; Bayu Aji Girawan; Linda Perdana Wanti; Nur Wachid Adi Prasetya; Ganjar Ndaru Ikhtiagung (Journal of Community Development, 2024)
Banjarwaru village is one of the villages in Cilacap district with the potential for wooden broom handle craft commodities. The processing of mahogany wood (Swietenia mahagoni) into broom handles produces wood waste that has not been utilized optimally. The accumulation of wood waste is caused by a lack of knowledge among the Banjarwaru village woodworking community regarding the potential dangers, benefits, and economic value of wood waste. Therefore, training in wood waste processing into value-added products such as particleboard is needed. The Community service team together with BUMDes Banjarwaru carried out mentoring activities as a solution method for utilizing wood waste. The mentoring activities carried out consist of educating the negative effects of wood waste on the environment, educating the potential and benefits of wood waste in another processed forms, and training in wood waste processing into particleboard. These series of activities succeeded in increasing the woodworking community understanding of wood waste by 81.6%. The success rate of mentoring reached 91,67% shown by 11 out of 12 mentoring participants understood the potential danger, benefits, and other processed forms of wood waste.